A green approach for the preparation of ZnO@C nanocomposite using agave americana plant extract with enhanced photodegradation. (10th December 2022) - Jakhrani, Mansab Ali; Tahira, Aneela; Bhatti, Muhammad Ali; Shah, Aqeel Ahmed; Shaikh, Nek Muhammad; Mari, Riaz Hussain; Vigolo, Brigitte; Emo, Mélanie; Albaqami, Munirah D; Nafady, Ayman; Ibupoto, Zafar Hussain
Abstract: The present study demonstrates the crucial role of agave americana extract in enhancing the optical properties of zinc oxide (ZnO) through thermal treatment method. Various analytical and surface science techniques have been used to identify the morphology, crystalline structure, chemical composition, and optical properties, including scanning electron microscopy, x-ray diffraction, high resolution transmission electron microscopy (HRTEM), x-ray spectroscopy (EDS) and UV–visible spectroscopy techniques. The physical studies revealed the transformation of ZnO nanorods into nanosheets upon addition of an optimized amount of agave americana extract, which induced large amount of amorphous carbon deposited onto ZnO nanostructures as confirmed by HRTEM analysis. The use of increasing amount of americana extract has significantly reduced the average crystallite size of ZnO nanostructures. The resultant hybrid system of C@ZnO has produced a significant effect on the ultraviolet light-assisted photodegradation of malachite green (MG) dye. The photocatalyst dose was fixed at 10 mg for each study whereas the amount of agave americana extract and MG dye concentration are varied. The functionality of hybrid system was greatly enhanced when the amount of agave americana extract increased while dye concentration kept at lower level. Ultimately, almost 100% degradation efficiency was achieved via the prepared hybrid material, revealing combined contribution from synergy, stabilization of ZnO due to excess of carbon together with the high charge separation rate. The obtained results suggest that the driving role of agave americana extract for surface modification of photocatalyst can be considered for other nanostructured photocatalysts.